SAMARALI FTALOTSIANIN PIGMENTLARINI SINTZ QILILISH VA TERMOGRAVAMETRIK TAHLILINI O’RGANISH - Sodiqov, Sardorbek; Beknazarov , Hasan (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
: In this article, the steps of synthesis of phthalocyanine pigment using effective methods and the necessary sharoids are presented, and thermogravimetric analysis of this pigment is studied.